2010
DOI: 10.1111/j.1461-0248.2009.01415.x
|View full text |Cite
|
Sign up to set email alerts
|

The intraspecific scaling of metabolic rate with body mass in fishes depends on lifestyle and temperature

Abstract: Metabolic energy fuels all biological processes, and therefore theories that explain the scaling of metabolic rate with body mass potentially have great predictive power in ecology. A new model, that could improve this predictive power, postulates that the metabolic scaling exponent (b) varies between 2/3 and 1, and is inversely related to the elevation of the intraspecific scaling relationship (metabolic level, L), which in turn varies systematically among species in response to various ecological factors. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
488
7
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(533 citation statements)
references
References 46 publications
37
488
7
1
Order By: Relevance
“…Several studies, however, offer alternative predictions [33 -36]. Glazier [37] and Killen et al [38] suggest that metabolic scalings not only are influenced by temperature and body mass, but that these scalings can be affected by the activity level and ecology of organisms. Glazier [37] has suggested that depending on the activity level of an animal, the scaling exponent can vary from 0.67 to 1; therefore, as metabolic (activity) level increases, the scaling exponent decreases from 1 to 0.67 and then starts to return to 1.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, however, offer alternative predictions [33 -36]. Glazier [37] and Killen et al [38] suggest that metabolic scalings not only are influenced by temperature and body mass, but that these scalings can be affected by the activity level and ecology of organisms. Glazier [37] has suggested that depending on the activity level of an animal, the scaling exponent can vary from 0.67 to 1; therefore, as metabolic (activity) level increases, the scaling exponent decreases from 1 to 0.67 and then starts to return to 1.…”
Section: Discussionmentioning
confidence: 99%
“…These fish had been collected from the wild and kept in near-identical conditions to the fish in the 308 309 310 311 312 313 314 315 316 317 318 319 320 321 322 323 324 325 326 327 328 329 330 331 332 333 334 335 336 337 338 339 340 341 342 343 344 current study and for a similar length of time. One possible explanation for this is that lentic sticklebacks develop more muscle than pond sticklebacks as a result having to swim against flowing water, which could increase their overall aerobic demand (Killen et al 2010). This could lead to them having to resort to anaerobic metabolism more often than lentic fish even in conditions where oxygen availability is relatively high, as it was for control fish in both the present and Sneddon and Yerbury's (2004) study.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in intraspecific scaling thus appears to be quite common and related to a set of connected biological and environmental factors (Glazier 2005). For example, variability in scaling exponents has been found to reflect organism lifestyle (Killen et al 2010), the physiological state of the organism (Glazier 2010), and ontogenetic shifts in habitat use (Riisgå rd 1998, Glazier 2005, Glazier 2006). Here, we assess whether variability in mass-metabolism scaling among conspecific populations can be explained by the ecological setting of its habitat, which has previously received relatively little study.…”
Section: Introductionmentioning
confidence: 99%